Investigation of the Nuclear Structure of 174-206Hg Isotopes Using Skyrme- Hartree-Fock Method - Radhi, R. A.; A. Alzubadi, Ali; F. Latooffi, Nabeel (Iraqi Journal of Science, 2023)
The effective Skyrme type interactions have been used in the Haretree-Fockmean-field model for several decades, and many different parameterizations of theinteraction have been realized to better reproduce nuclear masses, radii, and variousother data. In the present research, the SkM, SkM*, SI, SIII, SIV, T3, Sly4, Skxs15,Skxs20 and Skxs25 Skyrme parameterizations have been used within Haretree-Fock(HF) method to investigate some static and dynamic nuclear ground state propertiesof 174-206Hg isotopes. In particular, the binding energy per nucleon, proton, neutron,mass and charge densities and corresponding root mean square radii, neutron skinthickness and charge form factor. The calculated results are compared with theavailable experimental data. From present calculation, we can deduce that theSkyrme–Hartree–Fock (SHF) method with above parameterizations provide a gooddescription on the Hg isotopes.